About the interferences influence in the signal of a course radio beacon system on the accuracy of the automatic approach for landing of the aicraft - Полухін, Анатолій Васильович; Закалата, Дарина Юріївна; Ляховський, Василіос (Science-based technologies, 2020)
Flight safety assurance is an urgent and at the same time complex problem. Its complexity lies in the fact that the level of flight safety is determined by many factors. The main factors that significantly affect the level of flight safety include: the state of aviation equipment, the correctness of the aviation personnel actions, the state of the environment in which the operation of aviation equipment occurs, and others. Statistics shows that most of all accidents in the world’s air transport occur at the stages of approach and landing, because they are characterized by significant changes in speed, altitude, heading of the aircraft, the modes of engines operation, a change in configuration from flight- to landing- in conditions of psychological pressure on the crew the following factors: proximity to the earth and a small margin of speed and lack of time to analyze the situation and make decisions as to aircraft operation. The level of flight safety during the approach of an aircraft by a courseradio beacon system signal, together with other technical factors, is affected by the accuracy of the plane’s exit into the plane of the landing course and the accuracy of movement along it of view that the signal contains static and dynamic noise. To conduct a study of the dynamic noise influence in the signal of a course radio beacon system on the accuracy of an aircraft's automatic approach, the authors of the article developed a digital mathematical model of the flight dynamics of a medium-haul aircraft, that allows to study the processes of its by the accuracy of the plane’s exit into the plane of the landing course and the accuracy of movement along it of view that the course radio beacon system signal contains static and dynamic noise. The influence of the low-frequency and high-frequency interference in the course radio beacon system of the maximum intensity provided for by regulatory documents on the accuracy of the automatic approach of an aircraft has been studied. It has been shown that the specified interference has an insignificant effect on the aircraft’s trajectory parameters, but causes it to «swing» in lateral deviation from the plane of the landing course, in roll and heading with amplitudes that increase as the aircraft approaches the course radio beacon, while remaining within the limits allowed by regulatory documents.